Diversidad biológica y su conservación en una comunidad aledaña al puente Nanay. Loreto, 2024 - Upiachihua Arevalo, Julio Junior (2024)
The work carried out in the community of Santo Tomás, in Punchana, whose objective was to evaluate the perception of the population about biological diversity and its conservation in the Peruvian Amazon, in a sample of 197 heads of household, 60.4% say they know about biological diversity and 39.6% say that they do not know, in addition to that they have rarely observed diversity of fauna species in the forest. different fish in the rivers and lakes of the Peruvian Amazon, 43.7% and 50.3% respectively. In reference to the conservation of biodiversity in natural ecosystems, 57.4% report that forest fauna species should always be taken care of and 40.6% say, in many cases, that species should be conserved in their natural habitat. Regarding the urban development of the Amazonian peoples, they are aware that road works, such as the bridge over the Nanay River that connects their community with Bellavista, do not favor the conservation of ecosystems in 43.7% and others, such as 40.6%, rarely favor conservation, due to the fragmentation of habitats, migration and the disappearance of species. The population's perception of biological diversity and its conservation is acceptable, according to the results obtained in the research, as long as local institutions and governments reinforce knowledge on the subject.